PERANCANGAN DAN IMPLEMENTASI WLAN BERBASIS MIKROTIK MENGGUNAKAN METODE VLAN PADA PERUMAHAN MITRA CENTER SAGULUNG BATAM - Safutra, Muhammad Agus; Suharyanto, Cosmas Eko (Computer Science and Industrial Engineering, 2020)
Mitra Center is one of the residential areas in Sagulung District with a small area located in Kel. Sungai Langkai, Kec.Sagulung, Riau Islands, Batam City. Wired network infrastructure that is only provided by one ISP in this location has disappointed residents becouse has been limited. As a result residents buy a GSM data package that is also not cheap. Therefore researchers try to build a network based on Wireless Local Area Network (WLAN). Residents registered in this place are more or less 40 family cards (KK), the location of this place is classified as small and not extensive, which only has 4 blocks residential area. After conducting observations and interviews with several residents, consumption of internet access is relatively high, they are commonly complained when using GSM data packages becouse is not enough to buy once a month. Some of them interested using the wired internet provided by ISP like Indihome, but currently the available network is empty. Therefore, researchers designed a WLAN by utilizing an indihome connection that would be upgraded to 50Mbps to be allocated to WLAN users with a fair usage and optimization sharing mechanism, and adjusting needs based on data obtained during the data collection.